The Involvement of the Videographic Recording in the Happenings of Allan Kaprow. The Case of Print-Out (per George Brecht), Milan, 1971 (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
Between the end of the Sixties and the beginning of the following decade, Allan Kaprow’s research is in a phase of transition and change, where in his happenings he opens to an experimentation that goes beyond the characteristics of his first projects (the pure action) and incorporates the use of technological devices, in dialogue with the progress of events. In 1971 the city of Milan commissioned a happening dedicated to the city, the first in Italy: Print-Out (for George Brecht). This is one of the first works in which the artist relates a video recording to the realization of an action in one operation, and consequentially presents the tapes in an exhibition. However, the event had no echo, and lacked critical and historical interest, even by Kaprow himself, bringing it immediately to a sort of damnatio memoriae. The recent rediscovery of many materials and documents related to this happening has allowed, however, to conduct a philological reconstruction of the facts. This contribution aims to re-examine Print-Out and, at the same time, to analyse of how the artist employed the video, opening up his work to unprecedented possibilities of expansion of signification and experientiality of a happening-event-activity.
Keywords: Video Art; Milan; Video Installation